Computational and experimental study of air-core HTS transformer electrothermal behaviour at current limiting mode - Manusov, V. Z.; Kriukov, D. O.; Semenov, A. V. (Institute of Advanced Engineering and Science, 2021)
The paper provides the results of the experimental and computational study of the processes occurring in high temperature superconducting transformer windings while secondary winding is short-circuited. The obtained mathematical simulation matches closely with the experimental results. The temperature variation curves for superconducting windings were analysed, and conclusions were made on the necessity of changes in HTS transformer design, namely the necessity of windings heat-insulation from each other and adding a high-resistance coating material for HTS wire in HTS transformer primary winding.